Colocalization of Radicular Pain and Erythema Migrans in Patients With Bannwarth Syndrome Suggests a Direct Spread of Borrelia Into the Central Nervous System. (4th October 2021) - Ogrinc, Katarina; Kastrin, Andrej; Lotrič-Furlan, Stanka; Bogovič, Petra; Rojko, Tereza; Maraspin, Vera; Ružić-Sabljić, Eva; Strle, Klemen; Strle, Franc
Abstract: Background: There is a general assumption that after deposition into skin, Lyme borreliae disseminate hematogenously to other organs, resulting in extracutaneous manifestations of Lyme borreliosis, including Lyme neuroborreliosis. However, our experience over the past 40 years, along with several published case reports that observed colocalization of radicular pain and erythema migrans (EM) in patients with borrelial meningoradiculoneuritis (Bannwarth syndrome), argues against hematogenous dissemination in Lyme neuroborreliosis. Methods: We compared the location of EM in 112 patients with Bannwarth syndrome to 12315 EM patients without neurological involvement. Moreover, we assessed the colocalization of EM and radicular pain in patients with Bannwarth syndrome. Results: Compared to >12000 EM patients without neurological involvement, patients with Bannwarth syndrome had a significantly higher frequency of EM on head/neck (6% vs 1%; P =.0005) and trunk (47% vs 24%; P <.0001), similar frequency on arms (16% vs 16%; P =.91), but lower frequency on legs (30% vs 59%; P <.0001). Moreover, in 79% (89/112) of patients the site of EM matched the dermatomes of radicular pain. The odds for a congruent location of EM and radicular pain were highly significant with the highest odds ratios (OR) observed for head (OR=221), followed by neck (OR=159), legs (OR=69), arms (OR=48), and trunk (OR=33). Conclusions: The greater frequency of EM on head/neck and trunk and the colocalization of EM with radicular pain in patients with Bannwarth syndrome suggest that central nervous system involvement in Lyme neuroborreliosis is due to a retrograde spread of borrelia from skin to the spinal cord via peripheral nerves. Abstract : High spatial concordance of erythema migrans and radicular pain in patients with borrelial meningoradiculoneuritis (Bannwarth syndrome) suggests centripetal Borrelia spread from the skin to the spinal cord via peripheral nerves.